Triazine-Sulfonamide Hybrids: Synthesis, Antimicrobial Evaluation and In silico Investigation of their Potential Interaction with Dihydrofolate Reductase (DHFR) - Rani, Nisham; Mangla, Mohit; Sanduja, Mohit; Megha (Asian Journal of Chemistry, 2026)
Triazine–sulfonamide hybrids offer a versatile scaffold for antimicrobial drug, with the triazine core enabling structural modification and the sulfonamide group supporting target interactions. DHFR inhibition by these hybrids provides a rational strategy for developing new antimicrobial agents against the growing challenge of AMR. Hence, the present study focuses on the synthesis, structural characterization and evaluation of triazine–sulfonamide hybrids (A1–A12) for DHFR binding, supported by integrated in silico modelling and in vitro antimicrobial studies. Molecular docking with DHFR (PDB ID: 1RX3) showed good binding affinities (-8.5 to -10.2 kcal/mol), with key hydrogen-bonding interactions involving Asp27, Arg52, Arg57 and Ile94. Compounds A1 and A12 showed stronger binding than ciprofloxacin (-9.1 kcal/mol) and trimethoprim (-7.6 kcal/mol), which support its potential as DHFR-targeting antimicrobial candidates. In vitro antimicrobial screening via the tube dilution method demonstrated broad-spectrum potency across bacterial and fungal strains: compound A1 exhibited the lowest MIC against Escherichia coli (1.05 ± 0.06 µg/mL), compound A10 against Staphylococcus aureus (2.11 ± 0.08 µg/mL), compound A4 against Bacillus subtilis (2.14 ± 0.08 µg/mL) and Candida albicans (1.11 ± 0.05 µg/mL), compound A12 against Pseudomonas aeruginosa (1.19 ± 0.05 µg/mL) and compound A5 against Aspergillus niger (2.41 ± 0.09 µg/mL). Molecular dynamics (MD) simulations confirmed the dynamic stability and structural integrity of the top performing ligand DHFR complexes under simulated physiological conditions. DFT calculations provided insight into the frontier molecular orbitals and chemical reactivity descriptors, supporting the electronic stability and reactivity of the active scaffolds.